A Label-Free Quantitative Proteomic Analysis of Mouse Neutrophil Extracellular Trap Formation Induced by Streptococcus suis or Phorbol Myristate Acetate (PMA) - Wang, Xiaoping; Zhao, Jianqing; Cai, Cong; Tang, Xiaojuan; Fu, Lei; Zhang, Anding; Han, Li (Frontiers in Immunology, 2018)
Streptococcus suis (S. suis) ranks among the five most important porcine pathogens worldwide and occasionally threatens human health, especially in people who come into close contact with pigs or pork products. An S. suis infection induces the formation of neutrophil extracellular trap (NET) in vitro and in vivo, and the NET structure plays an essential role in S. suis clearance. However, the mechanism of NET induction remains to be elucidated. In the present study, we used a label-free quantitative proteomic analysis of mouse NET formation induced by S. suis or phorbol myristate acetate (PMA), a robust NET inducer. We found that more than 50% of the differentially expressed proteins of neutrophils infected by S. suis showed similar changes as PMA stimulation, and PKC, NADPH oxidase, and MPO were required for NET formation by both inducers. Because PMA could induce very obvious NET while S. suis (MOI=2) induced only weak NET, it was worth considering the association between the inducer and NET formation. Interestingly, proteins involved in peptidase activity showed significant differential changes in response to both inducers. Of these peptidases, MMP-8 expression showed obviously decreased in response to PMA, but it was not significantly changed in response to S. suis. The subsequent study further confirmed that MMP-8 activity was adverse for NET formation by both inducers, which suggested that regulation of these peptidases was one of the reasons for NET induction. Therefore, the present study provided important information about the manner in which neutrophils responded to the inducers to form NET.